ENHANCING MARKETING PERFORMANCE: MODERATION ROLE OF AI MARKETING STUDY AT PT. WORLD INNOVATIVE TELECOMUNICATIONS-OPPO BIG SEMARANG - Winarsih Winarsih; Fariha Azzahra; Andreas Onky A; Dela Tri Mulyani; Ira Serliyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Effective marketing strategies to optimize product sales are increasingly essential in facing of intensifying competition, particularly by focusing on marketing performance. The purpose of this study is to analyze the effects of product innovation strategy, digital marketing campaign, and customer engagement on marketing performance, as well as the moderating role of AI marketing in strengthening these relationships. This study adopts a quantitative research approach. Data were collected through a questionnaire, and the sampling technique employed was a census sampling method involving 225 respondents. Data analysis was conducted using the SEM-PLS method with SmartPLS 4.0 software. The findings reveal that product innovation and digital marketing campaigns do not have a significant effect on marketing performance, whereas customer engagement has a significant positive effect on marketing performance. Furthermore, the moderating role of AI marketing was found to be insignificant in enhancing the relationships between product innovation, digital marketing campaigns, and customer engagement on marketing performance.